1999
DOI: 10.1046/j.1526-4610.1999.3910728.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Migraine in Schoolchildren and Some Clinical Comparisons Between Migraine With and Without Aura

Abstract: The results of the present study show that migraine prevalence was 6.2% (95% confidence interval [CI], 5.4 to 7.0). The estimated prevalences of migraine with and without aura were 2.8% (95% CI, 2.3 to 3.4) and 3.4% (CI, 2.8 to 4.0), respectively. The prevalence of migraine increased with age and it was found to be almost equal in boys and girls aged 7 to 9 years or younger, but in older age groups the prevalence was higher in girls than in boys. The data showed no evidence that connected migraine with social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
3
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 24 publications
7
48
3
3
Order By: Relevance
“…It differs from the findings of most of the previous studies 8,13,17,19 which report prevalence of migraine from 6.2% to 10.4% and in a recent review, 3 which concluded that tension type headache is most common headache in children.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…It differs from the findings of most of the previous studies 8,13,17,19 which report prevalence of migraine from 6.2% to 10.4% and in a recent review, 3 which concluded that tension type headache is most common headache in children.…”
Section: Discussioncontrasting
confidence: 88%
“…Definition criteria that we had used could also be responsible for disparity as most of the studies that describe lower prevalence of migraine in adolescents than other headache were conducted prior to the publication of ICHD-2 8,13,17,19 and included relatively younger children. 8,13 Contrarily, one recent study that had followed ICHD-2 criteria 11 also reported higher prevalence of migraine. 7 In addition, a substantial number of children diagnosed of tension type headache in at least one previous study suffered nausea, pulsating headache, phonophobia and even photophobia.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of migraine was nearly equal in both genders before the age of 20 years (about 1:1) and the prevalence in females became progressively higher with age than males (1:2.6 between 25 and 30 years, up to 1:12.3 between 55 and 60 years). Mavromichalis et al 41 in their study on Greek school children reported equal prevalence of migraine among boys and girls. In contrast, Abu-Arefeh et al 1 reported a lower prevalence in girls than boys.…”
Section: Discussionmentioning
confidence: 93%
“…Population-based studies reported that the prevalence of migraine in childhood and adolescence ranges from 3% to 14% [1][2][3][4][5][6]. From the time of Wolff's early portrait of the childhood personality characteristics of migraine patients, the research began to explore the association of headache first with broad personality traits and then with distinct psychiatric symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%